Cloning and functional analysis of LH2, a gene controlling late heading in rice. Issue 4 (11th June 2021) - Dong, Shiqing; Sun, Dayun; Han, Xiaokang; Zhu, Yu; Niu, Fuan; Liu, Yang; Liu, Shuang; Sun, Xuejun; Ren, Ding; Hu, Zejun; Wang, Ying; Yan, Peiwen; et al.
Abstract: Heading date is an important agronomic trait in rice ( Oryza sativa L.). We previously fine‐mapped two complementary genes, Late Heading Date 1 and Late Heading Date 2 ( LH2 ), that control the late heading trait in rice. Here, we cloned and analyzed the function of LH2 . LH2 was fine‐mapped to a 53‐kb genomic region. Sequencing analysis revealed that there were differences in the coding sequence of LOC_Os08g07740 between the varieties 'Bo B' and 'Yuefeng B'. Therefore, LOC_Os08g07740 was identified as a candidate gene for LH2 and subsequently determined that LH2 is a Type 3 allele of Days To Heading 8 . Transgenic plants of Yuefeng B carrying LH2 from Bo B significantly delayed the heading date under short‐day and long‐day conditions. A yeast two‐hybrid analysis revealed that LH2 physically interacted with Heme Activator Protein (HAP) 5A, ‐H, ‐I, ‐L, ‐K, and HAP5‐LIKE. The HAP5 domain of HAP5 family members has various functions. Further analysis revealed that LH2 represses photoperiodic flowering by controlling the expression of Early Heading Date 1, Heading date 3a, and Rice Flowering Locus T1 in rice. Core Ideas: LH2 delayed heading by 17.6 d in short‐day conditions and >32.7 d in long‐day conditions. LH2 physically interacted with HAP5A, ‐H, ‐I, ‐L, ‐K, and HAP5‐LIKE. The HAP5 domain of the HAP5 family exhibited functional differentiation. LH2 is a Type 3 allele of DTH8 .